Hypersonic Flight Control with Inverse Dynamics Approach using FlightGear - Erwin Susanto; A. W. Pahlevi; M. R. Rosa (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2022)
Hypersonic flight is one of the technological developments for aircraft with speeds above Mach 5, the speed at which air separation begins to become significant. This paper presents a control of hypersonic flight with inverse dynamics systems. Hypersonic Flight Control (HFC) is approached as system and controlled by inverse dynamics. The design of the proposed inverse dynamics equation aims to cancel all nonlinear terms so that the closed loop system is linear, so that we can simulate the system in The control strategy aims to change quickly and accurately. The simulation result deployed by MATLAB shows the effectiveness of the proposed control scheme. We include FlightGear simulation to visualize the aircraft’s 3D motion. MATLAB and Simulink can be used for inverse dynamics control of hypersonic aircraft, while FlightGear can be used to visualize aircraft motion, making it easier to observe and verify control effectiveness. In the simulation, we use an altitude of 1000 with the PD controller gains Kp = diag(10; 10; 10; 10; 10; 20) and Kd = diag(10; 10; 10; 10; 10; 1) that gives less oscillation for the proposed scenario. We focused our research on the control of the aircraft using the Vector Field approach so that it solves the standard local minima problem in the path following method. The urgency of this research is crucial because it can revolutionize aircraft navigation and serve as a reference for the development of unmanned aircraft, shaping the future of world aviation.